History of pharmacy : pharmacy practice - Sachdeva, Rajive (New Delhi, India : Anmol Publications, 2010)
Pharmacy practice is the discipline of pharmacy which involves developing the professional roles of pharmacists.
Patient care -- Clinical Laboratory -- Basic Principles of Psychology -- Modes of Communication -- Prevention from infection -- Drug treatment in sports injuries -- Anti-anxiety drugs and sport -- Androgenic anabolic steroids
Includes index.
Keywords: PHARMACY HISTORY